Life Cycle Assessment for Supporting Eco-Design: The Case Study of Sodium–Nickel Chloride Cells - Sonia Longo; Maurizio Cellura; Maria Anna Cusenza; Francesco Guarino; Marina Mistretta; Domenico Panno; Claudia D’Urso; Salvatore Gianluca Leonardi; Nicola Briguglio; Giovanni Tumminia; Vincenzo Antonucci; Marco Ferraro (Energies, 2021)
The European Union is moving towards a sustainable, decarbonized, and circular economy. It has identified seven key value chains in which to intervene, with the battery and vehicle value chain being one of them. Thus, actions and strategies for the sustainability of batteries need to be developed. Since Life Cycle Assessment (LCA) is a strategic tool for evaluating environmental sustainability, this paper investigates its application to two configurations of a sodium–nickel chloride cell (planar and tubular), focusing on the active material and the anode, with the purpose of identifying the configuration characterized by the lowest environmental impacts. The results, based on a “from cradle to gate” approach, showed that the tubular cell performs better for all environmental impact categories measured except for particulate matter, acidification, and resource depletion. With nickel being the main contributor to these impact categories, future sustainable strategies need to be oriented towards the reduction/recovery of this material or the use of nickel coming from a more sustainable supply chain. The original contribution of the paper is twofold: (1) It enriches the number of case studies of LCAs applied to sodium/nickel chloride cells, adding to the few studies on these types of cells that can be found in the existing scientific literature. (2) The results identify the environmental hot spots (cell configuration and materials used) for improving the environmental footprint of batteries made from sodium/nickel chloride cells.